(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article analyzes the genesis of the study of orthological issues in Uzbek, European, American and Russian linguistics. At the same time, the scientific basis is given that the system of syntactic, semantic, stylistic characters, which is necessary to form the main part of orthological dictionaries, is studied in World linguistics. Scientific views are described about complex and professional dictionaries, which are part of the linguistic composition of orthological dictionaries.